Penciptaan Tari Rambasaka Kabokemu Ikatan Perempuan yang Ingin Lepas dari Tindakan KDRT - Waode Muriani Ekasari Virno Bolu (Journal on Education, 2023)
In Butonese, untying is rambasaka kabokemu. The dance work's choreography is inspired by criticism of the phenomenon of violence against women. The rise of the issue of violence against women makes dancers reveal the other side of women who are trying to break free from shackles. Rambasaka Kabokemu is danced by male and female dancers who depict an abusive relationship with visual media forms. The creation method used in this work is "Creating Thourgh Dance" by Alma M. Hawkins, explained that there are three stages: the exploration stage, the improvisation stage and the formation stage. These three stages are closely related to one another with their implementation. Rambasaka Kabokemu is the third work done with a dramatic concept. This dance work can provide benefits for stylists and other people. For dancers, it is useful to raise new awareness about the fate and condition of women who have experienced acts of violence and want to voice their opinions.